Knowledge Management Practices On Large-Scale Construction Projects In An Australian Company: An Ethnographic Study - Nycyk, Michael (Journal of Knowledge Management Practice, 2011)
A three and a half year ethnographic study of knowledge management practices on Australian large-scale projects observed professionals at work in the design and construction within one company over one such project. This study shows how knowledge is captured, exchanged and transmitted on fast-paced construction projects, supported by interviews, descriptions and document analysis. It also discusses factors that impede and support knowledge management, and also takes into account issues of technology, cultural differences in valuing knowledge management, and the codifying of knowledge and relationships. This study concludes with a discussion of results and implications for both knowledge management in construction industries, and for undertaking ethnographic research.
Keywords: knowledge management; Ethnography; Knowledge management practices; Construction industry; Knowledge management systems